New approach for removing the self-heating from MOSFET current using only DC characteristics - Mori, C. A. B.; Agopian, P. G. D. [UNESP]; Martino, J. A.; IEEE (Ieee, 2018)
In this paper we report a new technique for removing the self-heating from the DC output characteristics of a MOSFET. In this method, the self-heating is eliminated from the drain current through a mathematical procedure, allowing a direct comparison of the curves with and without self-heating. We developed an analytical model considering the temperature increase in the channel of devices due to self-heating which causes the mobility degradation. To apply this technique, the inverse transistor efficiency method was employed to obtain the thermal resistance (using only DC measurements) and the temperature mobility degradation factor. In the worst case for tridimensional simulations of Silicon-On-Insulator FinFET devices, we obtained an error of 3.6% between the drain current with the self-heating eliminated through our method and the current without self heating. Additionally, when we applied the method to devices without self-heating, the drain current presented no changes, showing that the method can determine if a device is self-heating free or not.
Keywords: self-heating effect; Silicon-On-Insulator; FinFET